Safety and effectiveness of a long, partially covered metal stent for endoscopic ultrasound-guided hepaticogastrostomy in patients with malignant biliary obstruction - Nakai, Yousuke; Isayama, Hiroyuki; Yamamoto, Natsuyo; Matsubara, Saburo; Ito, Yukiko; Sasahira, Naoki; Hakuta, Ryunosuke; Umefune, Gyotane; Takahara, Naminatsu; Hamada, Tsuyoshi; Mizuno, Suguru; Kogure, Hirofumi; Tada, Minoru; Koike, Kazuhiko (Endoscopy, 2016)
Background and study aims: Endoscopic ultrasound (EUS)-guided biliary drainage (EUS-BD) is potentially complicated by bile leak and stent migration. The aim of this study was to evaluate the safety and effectiveness of a long (≥ 10 cm), partially covered metal stent (LP-CMS) for EUS-guided hepaticogastrostomy (EUS-HGS) for malignant biliary obstruction. Both the stent length and the uncovered portion at the proximal end of the LP-CMS are designed to prevent stent migration. Patients and methods: A total of 33 patients undergoing EUS-HGS using an LP-CMS in four centers were retrospectively studied. Technical and clinical success, adverse events, and recurrent biliary obstruction were evaluated.Results: Gastric outlet obstruction (76 %) and surgically altered anatomy (15 %) were two major reasons for EUS-HGS. The technical and clinical success rates were 100 %. The median intragastric stent length was 54 mm. The adverse event rate was 9 %. No stent migration was observed. Recurrent biliary obstruction developed in 24 %, with a median cumulative time to recurrence of 8.5 months.Conclusions: EUS-HGS using an LP-CMS for unresectable malignant biliary obstruction was safe and effective.